Research on key functions locating technique based on software execution trace difference comparison - Fei KANG; Qian WANG; Ya-nan XIAO; He-jie HUANG (Tongxin xuebao)
Key functions are the core functions which play vital es in certain run phase of application software.The quick locating of key functions is a valid method to improve the efficiency of software reverse analysis.In the field of software reverse engineering,locating key functions is mostly based on l analysis.Dynamic binary Instrumentation (DBI) techniques were employed to present a practicabletechnique to automatically locating the key functions based on software execution trace difference.Key functions can be quickly and precisely located when key functions can be triggered or not by two different kinds of software inputs.